2013
DOI: 10.1177/0018726713479620
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid accountabilities: When western and non-western accountabilities collide

Abstract: This article critiques the international development sector by questioning the role of western reporting practices in establishing accountability between non-western stakeholders. Homi Bhabha’s theoretical framework on translation and hybridity is applied to understand how recipient NGO workers experience western forms of accountability, such as English-written reports. Drawing on ethnographic research carried out in an Indian NGO, three key findings are outlined. First, reporting subjugates local knowledge le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 39 publications
(45 reference statements)
0
55
0
Order By: Relevance
“…()—ability, benevolence, and integrity—may vary significantly from a culture in a developed economy to one in a developing economy. We anticipate that these distinctions will be material to future scholarship, consistent with the ways that Dar () has interrogated the interplay of written language and indigenous customs, resulting in what she calls “multivocal” communication. An in‐depth understanding of the emic composition of these three components may prove vital for the initial creation and ongoing maintenance of trust within organizations.…”
Section: Directions For Future Researchmentioning
confidence: 60%
See 1 more Smart Citation
“…()—ability, benevolence, and integrity—may vary significantly from a culture in a developed economy to one in a developing economy. We anticipate that these distinctions will be material to future scholarship, consistent with the ways that Dar () has interrogated the interplay of written language and indigenous customs, resulting in what she calls “multivocal” communication. An in‐depth understanding of the emic composition of these three components may prove vital for the initial creation and ongoing maintenance of trust within organizations.…”
Section: Directions For Future Researchmentioning
confidence: 60%
“…In encouraging similar emic studies, Tsui () advocates for what she terms “indigenous” research, aimed at theory development within the context of specific cultures. Contributing additional contextualized scholarship to existing Northern or Western catalogs will only serve to enhance our understanding of diverse typologies and allow us more effectively to integrate these competencies into a comprehensive and holistic perspective on trust (see also Dar ).…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…It is well to remember that as a developing country, Fiji has enjoyed a considerable period of time during which many of its entities have relied on a traditional form of reporting where there is a reliance on oral communication and deference to custom rather than written Western forms of reporting as advanced by the Western industrial nations (Brown, ). Dar () looked at the link between Western reporting practices and accountability and found that Western reporting subjugates local knowledge, leading to local employees' sense of disempowerment. These workers produce hybrid accounts in response to these imported reporting practices that help build donor and local trust practices.…”
Section: Resultsmentioning
confidence: 99%
“…The potential access to external funding might trigger 'strategies of extraversion' of elites (Bayart, 1993;Chabal and Daloz, 1999, p. 22) and, thus consolidating local hegemonies. Moreover, the practices tied to these resources, such as the models of project management, monitoring and evaluation required by the Northern collaborators are, on their part, main means to reproduce donor hegemonies (Igoe, 2003;Dar, 2014;Girei, 2016;Mueller-Hirth, 2012;Claeyé and Jackson, 2012). Simultaneously, they might offer pockets of counter-hegemonic transformation (cf.…”
Section: Organizing Processes: Establishing Structures Around Shared mentioning
confidence: 99%